Meningkatkan Loyalitas Nasabah dengan Service Excellent dan Dimediasi oleh Kepuasan Nasabah - Oktariyani, Ni Putu; Benni Kusyana, Dewa Nyoman (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The village credit institution is a non-bank financial institution that is managed independently by a traditional village. These financial institutions also have to face intense competition from other formal financial institutions, so it is very important to maintain the loyalty of their customers. This research was conducted to determine the effect of excellent service on customer loyalty directly and mediated by customer satisfaction. The LPD Desa Pakraman Kutri was designated as the research location with a total of 952 customers in 2021, so a sample of 100 customers was determined using the Slovin Formula. Sampling was done by accidental sampling technique. The three direct effect hypotheses were tested by path analysis, and the mediation test was carried out by the Sobell test. The results of the study prove that an increase in service excellent and customer satisfaction will significantly increase customer loyalty, an increase in customer satisfaction will be followed by a significant increase in customer loyalty, and the effect of service excellent on customer loyalty customer satisfaction is mediated by customer satisfaction.